THE BEGINNINGS OF MODERN SERBIAN ART EDUCATION IN KOSOVO AND METOHIJA (Heritage, 2023)
The beginnings of contemporary Serbian art in Kosovo and Metohija are related to the establishment of the first educational institutions in this area, where generations of students and art  studenst were educated. And overview of  the development of contemporary art in Kosovo and Metohija can be traced back to 1949, when the High School of Art was founded in Peć. This school becomes a nursery of talents and a center of artistic development, imrovement and shaping of artistic reality and Kosovo and Metohija. After that, the development of art education was infuenced by the  establishment of the Higher  Pedagogical School in Pristina in 1962. The conception of this educational institution included the formation of the Fine Arts Group, where young  artists were successfully trained. The Academy of Arts in Pristina was re – established  in 1973 an it had the following educational  courses painting, sculpture, graphics and graphic design. The Academy played a key role in the development of the art scene in the province, educating young artists and future art teachers. Since the school year 1986/87, the Academy was reorganized and continued to work as the Faculty of Arts in Pristina. The most difficult period in the history of university art education in the province ocurred  due to the war events in 1999, when the professors and students of this higher  education institution were expeled. The facultys infastructure, teaching space and studios were usurped, and most of works of art were looted and destroyed.  The Faculty of Arts was then moved first to central Serbia, and cince 2001. It has been working in Zvečan , i.e  Kosovska Mitrovica.
Keywords: Kosovo and Metohija, Serbs, contemporary art, school, education.